Impact of retinal traction induced by epiretinal membrane on aniseikonia - Hirano, Masayuki; Minakawa, Shun; Imamura, Yuta; Yamamoto, Naoko (Scientific reports, 2024)
We investigated the effect of retinal traction caused by epiretinal membranes (ERMs) on aniseikonia and retinal microstructures in 81 unilateral ERMs. Retinal traction was quantified by measuring the maximum depth of the retinal fold (MDRF) using en face optical coherence tomography (OCT) images. Measurements included the mean inner nuclear layer (INL), outer plexiform layer (OPL), outer nuclear layer (ONL), central retinal thickness (CRT), and interocular ratios of the foveal avascular zone (FAZ) area (FAZ ratio). Significant correlations were found between the preoperative MDRF and preoperative aniseikonia ( P < 0.001), INL thickness ( P < 0.001), CRT ( P < 0.001), and FAZ ratio ( P = 0.003). Preoperative aniseikonia was significantly correlated with preoperative INL and OPL-ONL thicknesses ( P < 0.001 and P = 0.020, respectively) and CRT ( P = 0.003). Multiple regression analysis revealed that preoperative aniseikonia was significantly associated with preoperative MDRF, INL, and OPL-ONL thicknesses ( P = 0.029, 0.006, and 0.006, respectively). Twenty-nine eyes underwent membrane peeling, resolving all retinal folds 6 months postoperatively. A significant correlation was observed between preoperative MDRF and postoperative aniseikonia ( P = 0.011). Our findings suggest that retinal traction by ERM is significantly associated with aniseikonia both pre- and postoperatively, alongside other OCT parameters.